Defining urban design in the Chilean context: the contributions of Munizaga - de Souza, Gisela Barcellos; Tine Gimenez, Andre (International Planning History Society Proceedings, 2018)
We intend to contribute to the understanding of the initial paths and penetration routes Urban Design and Urbanistic Project notions in the urban and architectural culture in Latin America. To this end, it focuses on the trajectory and intellectual work of a Chilean architect, Gustavo Munizaga, who was responsible for writing one of the first didactic texts on urban design in Latin America and did so contemporaneously with the first manifestations of the Modern Movement’s critical revision and the typomorphological approach in Chile.